Engineering monodispersed 2 nm Sb2S3 particles embedded in a porphyrin-based MOF-derived mesoporous carbon network via an adsorption method to construct a high-performance sodium-ion battery anode. Issue 33 (27th July 2022) - Zhao, Shuya; Jia, Hongna; Wang, Yao; Ju, Na; Zhang, Xinyue; Guo, Ying; Wang, Yiming; Wang, Haipeng; Niu, Suyan; Lu, Yanming; Zhu, Lin; Sun, Hong-bin
Abstract : 2 nm Sb2 S3 particles embedded in a mesoporous carbon framework by an adsorption method to construct a high performance anode material. Abstract : Sodium ion batteries (SIBs) are expected to replace lithium ion batteries (LIBs) as the next generation of large-scale energy storage applications because of their superior cost performance. However, the larger ionic radius of Na + causes a remarkable volume expansion than that of Li + during charge and discharge, which reduces the performance of the battery. In this work, we engineered a composite material in that monodispersed 2 nm Sb2 S3 particles are uniformly loaded into a carbon matrix (Sb2 S3 /CZM), which is obtained by carbonization of a zirconium-based MOF with adsorption of Sb. The obtained composite material has a high specific surface area in favor of mass transfer, and the porous structure can resist many volume changes in the circulation process. Moreover, the ultrafine Sb2 S3 particles are well-distributed in the composite material, which increases the utilization of the active substance and is promising for the storage of Na + . Based on its unique structure, the Sb2 S3 /CZM composite shows a specific capacity of 550 mA h g −1 at 100 mA g −1 and an excellent cycling stability of 88.9% retention after 1000 cycles at 3 A g −1 . The excellent electrochemical performance provides enlightenment for the rational design of hierarchical heterostructures for energy storage applications.